(untitled) - Toynbee, Arnold J. (London, 1939)
The problem of the Disintegrationsof civilizations; The nature of Disintegrations of civilizations; The cause of the Disintegrations of civilizations.
Keywords: Civilization,Nền văn minh; History,Lịch sử